Animal Models of GWAS-Identified Type 2 Diabetes Genes. (22nd April 2013) - da Silva Xavier, Gabriela; Bellomo, Elisa A.; McGinty, James A.; French, Paul M.; Rutter, Guy A.
Abstract : More than 65 loci, encoding up to 500 different genes, have been implicated by genome-wide association studies (GWAS) as conferring an increased risk of developing type 2 diabetes (T2D). Whilst mouse models have in the past been central to understanding the mechanisms through which more penetrant risk genes for T2D, for example, those responsible for neonatal or maturity-onset diabetes of the young, only a few of those identified by GWAS, notably TCF7L2 and ZnT8/SLC30A8, have to date been examined in mouse models. We discuss here the animal models available for the latter genes and provide perspectives for future, higher throughput approaches towards efficiently mining the information provided by human genetics.